Impact of Human Immunodeficiency Virus–Related Gut Microbiota Alterations on Metabolic Comorbid Conditions. (2nd January 2020) - Gelpi, Marco; Vestad, Beate; Hansen, Simen Hyll; Holm, Kristian; Drivsholm, Ninna; Goetz, Alexandra; Kirkby, Nicolai Søren; Lindegaard, Birgitte; Lebech, Anne-Mette; Hoel, Hedda; Michelsen, Annika E; Ueland, Thor; et al.
Abstract: Background: We aimed to identify a human immunodeficiency virus (HIV)–related microbiota signature, independent of sexual preferences and demographic confounders, in order to assess a possible impact of the microbiome on metabolic comorbid conditions. Methods: Bacterial 16S ribosomal RNA analyses were performed on stool samples from 405 HIV-infected and 111 uninfected participants of the Copenhagen Comorbidity in HIV Infection (COCOMO) study. Individuals were stratified according to sexual behavior (men who have sex with men [MSM] vs non-MSM). Results: After excluding MSM-associated microbiota traits and adjusting for confounders, we identified an HIV-related microbiota signature, consisting of lower biodiversity, increased relative abundance of the bacterial clades Gammaproteobacteria and Desulfovibrionaceae and decrease in several Clostridia. This microbiota profile was associated with a 2-fold excess risk of metabolic syndrome, driven by increase in Desulfovibrionaceae and decrease in Clostridia (Butyrivibrio, Coprococcus 2, Lachnospiraceae UCG-001 and CAG-56). This association was accentuated (5-fold excess risk) in individuals with previous severe immunodeficiency, which also modified the association between HIV-related microbiota signature and visceral adipose tissue (VAT) area ( P for interaction = .01). Accordingly, HIV-related microbiota was associated with 30-cm 2 larger VAT in individuals with history of severe immunodeficiency, but not in those without. Conclusion: The HIV-related microbiota was associated with increased risk of metabolic syndrome and VAT accumulation, particularly in individuals with previous severe immunodeficiency, driven by increased Desulfovibrionaceae and lower abundance of several Clostridia. Our findings suggest a potential interplay between HIV-related microbiota, immune dysfunction and metabolic comorbid conditions. Interventions targeting the gut microbiome may be warranted to reduce cardiovascular risk, particularly in individuals with previous immunodeficiency. Abstract : Human immunodeficiency virus–related microbiota alterations were associated with visceral fat accumulation and metabolic comorbid conditions, particularly in individuals with previous severe immunodeficiency.